γ-Secretase modulators exhibit selectivity for modulation of APP cleavage but inverse γ-secretase modulators do not - Christian B. Lessard; Edgardo Rodriguez; Thomas B. Ladd; Lisa M. Minter; Barbara A. Osborne; Lucio Miele; Todd E. Golde; Yong Ran (Alzheimer’s Research & Therapy, 2020)
Abstract Background γ-Secretase is a multiprotein protease that cleaves amyloid protein precursor (APP) and other type I transmembrane proteins. It has two catalytic subunits, presenilins 1 and 2 (PS1 and 2). In our previous report, we observed subtle differences in PS1- and PS2-mediated cleavages of select substrates and slightly different potencies of PS1 versus PS2 inhibition for select γ-secretase inhibitors (GSIs) on various substrates. In this study, we investigated whether γ-secretase modulators (GSMs) and inverse γ-secretase modulators (iGSMs) modulate γ-secretase processivity using multiple different substrates. We next used HEK 293T cell lines in which PSEN1 or PSEN2 was selectively knocked out to investigate processivity and response to GSMs and iGSMs. Methods For cell-free γ-secretase cleavage assay, recombinant substrates were incubated with CHAPSO-solubilized CHO or HEK 293T cell membrane with GSMs or iGSMs in suitable buffer. For cell-based assay, cDNA encoding substrates were transfected into HEK 293T cells. Cells were then treated with GSMs or iGSMs, and conditioned media were collected. Aβ and Aβ-like peptide production from cell-free and cell-based assay were measured by ELISA and mass spectrometry. Result These studies demonstrated that GSMs are highly selective for effects on APP, whereas iGSMs have a more promiscuous effect on many substrates. Surprisingly, iGSMs actually appear to act as like GSIs on select substrates. The data with PSEN1 or PSEN2 knocked out HEK 293T reveal that PS1 has higher processivity and response to GSMs than PS2, but PS2 has higher response to iGSM. Conclusion Collectively, these data indicate that GSMs are likely to have limited target-based toxicity. In addition, they show that iGSMs may act as substrate-selective GSIs providing a potential new route to identify leads for substrate-selective inhibitors of certain γ-secretase-mediated signaling events. With growing concerns that long-term β-secretase inhibitor is limited by target-based toxicities, such data supports continued development of GSMs as AD prophylactics.